Metabolic and molecular effects of dietary extra virgin olive oil in blood and placenta of women with GDM - Gomez Ribot, Dalmiro; Diaz, Esteban; Fazio, María Victoria; Gómez, Hebe Lorena; Careaga, Valeria; Maier, Marta; Macchi, Silvia Beatriz; Gresta, Carlos Alberto; Capobianco, Evangelina; Jawerbaum, Alicia (Frontiers in Endocrinology, 2023)
Gestational diabetes mellitus (GDM) increases the risks of maternal, placental and neonatal complications. Previously, we found that a diet enriched in extra virgin olive oil (EVOO) prevents increased maternal triglyceridemia and placental proinflammatory markers in a cohort of GDM patients. The aim of this work was to evaluate maternal circulating markers of insulin resistance, placental collagen, glycogen and lipid levels, and placental levels of proteins, mRNAs and a microRNA involved in the endocytic pathway in the same cohort of control women and women with GDM who received or not a diet enriched in EVOO (36 g/day) from weeks 24 to 28 of pregnancy until term. At term, the TG/HDL cholesterol ratio, fatty acid binding protein 4 circulating levels and maternal BMI were increased in the GDM patients, alterations prevented by the maternal diet enriched in EVOO. Although there were no changes in placental lipid levels and lipid profile, GDM placentas were thicker than controls and showed increased glycogen and collagen content, alterations prevented by the EVOO-enriched diet. GDM placentas showed increases in megalin levels, in the expression of several genes involved in the endocytic pathway, and in miR-199, which targets these genes, alterations prevented by the maternal diet enriched in EVOO. Altogether, we identified novel beneficial effects of an EVOO-enriched diet in GDM women, a diet capable of regulating maternal insulin resistance, the structure and metabolism of the placenta and the placental endocytic pathway, suggesting effects that may be beneficial for fetal development.